Relationship between Community Participation, Socio Economy and Organizational Capacity on Sustainable Development - Amin, Aziz; Puad Mat Som, Ahmad; Ibrahim, Yahaya; Shaladdin Muda, Mohd (International Journal of Engineering and Technology, 2018)
This paper attempts to understand the influence of community participation, socio-economy and organizational capacity on the sustainability of community based tourism, focusing on homestay programs. This study has gathered data from 96 homestayâ€™s operators from northern states of peninsular Malaysia. This study used path analysis approach to determine community participation and socio-economy factors that trigger organizational capacity and sustainable development. Based on the results, community participation and socio-economy are correlated in indirect effect with sustainable development through organizational capacity. Thus the path-analysis indicates that the engagement of organizational capacity in the homestay program will correlate community participation and socio-economy toward sustainable development.Â